Effects of source and level of dietary lysine on growth performance of pigs from 24 to 48 lb - E L Hansen; J C Woodworth; P R O'Quinn; La Llata M De; M U Steidinger; Michael D Tokach; Robert D Goodband; Jim L Nelssen; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 1999)
Three hundred twenty, 24 lb nursery pigs were fed for 19 days to compare the effects of increasing dietary lysine from L-Iysine HCl (L-Lys) or Peptide Plusâ„¢ (PP) on growth performance. Three dietary treatments (1.025, 1.15, and 1.275% lysine) were each formulated with L-Lys and PP. Negative and positive control corn-soybean meal-based diets were formulated to .90 and 1.275% lysine, respectively. Increasing dietary lysine to 1.275% from L-Lys or PP resulted in increased performance; however, pigs fed the positive control diet had the best overall performance.; Swine Day, Manhattan, KS, November 18, 1999
Keywords: Swine day; 1999; Kansas Agricultural Experiment Station contribution; no. 00-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 841; Swine; Lysine; L-lysine HCl; Peptide plus; Pigs